KARAKTERISTIK TEGANGAN TEMBUS MINYAK TRAFO SHELL DIALA B MENGGUNAKAN MATERIAL ELEKTRODA BERBAHAN STAINLES STEEL, KUNINGAN, TEMBAGA DAN ALUMUNIUM - Amali, Kamil; Mohamad, Yasin; Yusuf, Taufik Ismail; Ntobuo, Nova Elysia (Journal Of Renewable Energy Engineering, 2024)
Transformer oil insulation breakdown voltage testing is usually carried out at high AC voltage using the SPLN 49-1 1982 standard. The electrodes used are hemispherical electrodes with a distance between the electrodes of 2.5mm. The breakdown voltage value of transformer oil insulation that meets the standards according to SPLN 49-1 of 1982 is 30 kV/2.5mm. In this research, a new Shell Diala B brand transformer oil insulation breakdown voltage test was carried out using the SPLN 49-1 1982 testing standard. The novelty of this research is using various electrode shapes and different electrode materials to test the breakdown voltage of the transformer oil's liquid insulation. The method used in this research is an experimental method where the test is adapted to the SPLN 49-1 standard of 1982. The electrodes used are ball, needle, and plate electrodes. Based on test results at a distance between electrodes of 2.5 mm, it was found that the breakdown voltage characteristics of stainless steel, brass, copper, and aluminum electrode materials varied and did not meet the SPLN 49-1 1982 standard, namely 30 kV/2.5 mm.